Vogt-Koyanagi-Harada Disease Associated with Rheumatoid Arthritis - Hasan Ali TUFAN,; Ayla AKBAL,; Sedat ARIKAN,; Baran GENCER,; Selçuk KARA,; Abdurrahman TUFAN3, (Archives of Rheumatology, 2013)
A 31-year-old male patient was admitted to our eye clinic with the complaints of bilateral blurred vision and photophobia. He also suffered from a severe headache, tinnitus, morning stiffness, and arthralgias. His medical history revealed that he had been receiving care for rheumatoid arthritis (RA) for eight years. The best corrected visual acuity was 20/50 in the left eye and 20/40 in the right. His ocular examination revealed bilateral panuveitis with serous retinal detachment. Optical coherence tomography (OCT) confirmed the presence of bilateral subretinal fluid, while fluorescein angiography (FA) demonstrated a “starry sky” appearance and optic disc staining. The patient was diagnosed with Vogt-Koyanagi-Harada (VKH) disease based on the clinical, FA, and OCT findings. In conclusion, both RA and VKH disease share many similar genetic and environmental factors in their etiopathogenesis. Therefore,further investigations are required to confirm the association between these two autoimmune diseases.